(untitled) (International journal of medical sciences, 2026)
This article analyzes the methodological foundations for developing creative thinking among students in the process of teaching Histology. In modern medical education, along with mastering theoretical knowledge, it is essential to develop students’ independent, critical, and creative thinking skills. The study evaluates the effectiveness of problem-based learning, cluster methods, case studies, digital microscopy, 3D modeling, and interactive platforms based on experimental research. The results demonstrate that classes organized on the basis of creative approaches significantly improved students’ academic performance and analytical thinking.